Determinants of Labor Demand in The Islands (A Study of 11 Regencies / Cities in Maluku Province) - Hahury, Hendri D; Oppier, Hermi; Pattimahu, Terezia V; Malawau, Imanuela G (Indonesian Journal Publisher, 2024)
The composition of regional products according to economic sectors may generally reveal a region’s economic structure, therefore the number of workers employed in the economic sector can be interpreted as an indicator of the economic sector’s workforce absorption potential. The purpose of this study is to identify and assess determinants of labor demand (open unemployment, Human Development Index (HDI), and minimum wage) in the islands, specifically Maluku Province which consists of 11 regencies / cities. This study employed a descriptive-quantitative method, employing a multiple linear regression analysis. The results show that the open unemployment, HDI, and minimum wage have a negative and insignificant impact on the labor demand in the islands. In fact, labor demand issues in the islands were more complex than in continental areas, such as regional egocentrism, which expected the “local community youth” to have priority in the labor demand yet they had no skill mastery. As a result, investing in education through “specialization” of labor was predicted to be critical to the labor absorption.